2020
DOI: 10.1080/08961530.2020.1717400
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Destination Brand Personality on Chinese tourists' Revisit Intention to Glasgow: An Examination across Gender

Abstract: The aim of this research is to examine the mediating effects of self-congruity between destination brand personality, to revisit intention and heed the moderating effects of gender between self-congruity. Therefore, data were collected through a survey from 226 Chinese outbound tourists in Glasgow city, United Kingdom and was analysed to provide evidence.Based on the results, the analysis of partial least squares structural equation modelling (PLS-SEM) using the Smart PLS 3.0 program indicated that self-congru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 95 publications
(145 reference statements)
3
32
0
1
Order By: Relevance
“…Liu et al, 2019;N. Su & Reynolds, 2017;Usakli & Baloglu, 2011;Yang et al, 2020). More importantly, modeling also indicated that destination personality has an indirect effect on the intention to revisit as well as intention to recommend through self-congruity.…”
Section: Destination Personality Self-congruity and Behavioral Intementioning
confidence: 89%
See 4 more Smart Citations
“…Liu et al, 2019;N. Su & Reynolds, 2017;Usakli & Baloglu, 2011;Yang et al, 2020). More importantly, modeling also indicated that destination personality has an indirect effect on the intention to revisit as well as intention to recommend through self-congruity.…”
Section: Destination Personality Self-congruity and Behavioral Intementioning
confidence: 89%
“…Therefore, self-congruity is known to have a direct effect on behavioral intention. Particularly, a relatively small number of tourism studies managed to confirm the relationship between self-congruity and intention to revisit (Kiliç & Sop, 2012;Yang et al, 2020) as well as intention to recommend (W. Kim & Malek, 2017;Rutelione et al, 2018). Others also established the relationship between self-congruity and tourist loyalty (i.e., revisit intention and recommend intention; Sop & Kozak, 2019).…”
Section: Destination Personality Self-congruity and Behavioral Intementioning
confidence: 99%
See 3 more Smart Citations